Metode Pembelajaran Inquiry dan Pengaruhnya terhadap Hasil Belajar Matematika ditinjau dari Kreativitas Belajar - Roida Eva Flora Siagian; Maya Nurfitriyanti (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2012)
Purpose of this study was to determine the effect of the inquiry learning method and creativity on learning to mathematics learning. This research was an experimental study with research design two way anova. This research did on Indraprasta University students with 68 persons. From this research we know that: 1) any effect of the inquiry learning method to mathematics learning, 2) any effect of creatifity on learning to mathematics learning, 3) any effect of interaction inquiry learning method and creativity on learnning to mathematics learning, 4) any significant effect of inquiry learning method with conventional learning method to students which have high creativity, 5) no significant effect of inquiry learning method with conventional learning method to students which have low creativity, 6) any significant effect of student mathematics learning which have high creativity and low creativity on teached by inquiry method, and 7) no significant effect of student mathematics learning which have high creativity and low creativity on teached by conventional method.